КМОП БИС 16-разрядного микропроцессора, устойчивого к воздействию γ-радиации - Verbitsky, V. G.; Zolotarevsky, V. I.; Samotovka, L. I.; Balay, B. A.; Voshchinkin, A. F.; Koba, V. L.; Tovmach, E. S.; Yavetsky, A. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The results of design and testing of the CMOS IC 1834VM86 16-bit microprocessor (a functional analogue of the n-channel IC 1810VM86) under exposure to accumulated γ-radiation doses up to 10⁶ rad are presented. The structural features of the elements and the technological process of manufacturing radiation-resistant ICs are discussed. Values of the main electrical parameters of the IC and threshold voltages of n-channel transistors before and after radiation-thermal treatments during crystal fabrication are provided.